Personal resilience strategies women leaders use to navigate gender discrimination in South African manufacturing organisations - Mareletse, Disebo (University of Pretoria, 2024)
The country has made significant progress with women entering STEM fields. However, women who choose male-dominated occupations in industries such as manufacturing soon change to more inclusive and gender-balanced fields, making female retention and attraction difficult for the sector. This leads to a brain drain that plays a pivotal role in an already declining industry. Cultural expectations and gender stereotypes are among some of the challenges women grapple with in the industry, delaying progress towards a more diverse, equitable and inclusive sector. The purpose of the narrative inquiry was to understand the resilience strategies women leaders use to navigate gender discrimination in the manufacturing sector in South Africa, to help bridge the disconnect between government policies and current organisational practices in the industry. This was achieved through a qualitative research methodology examining the lived experiences of 15 women leaders within the industry. The findings indicated that that women are still subjected to systemic barriers preventing their progression within the industry. Due to lack of organisational support women develop different adaptive strategies such of Ubuntu leadership style, seeking a strong community of support, which is enabled by a healthy workplace culture. The intersectionality between race and gender highlighted the severity of gender discrimination for previously marginalised groups. Creating the urgency needed for manufacturing organisations to re-evaluate the effectiveness of their organisational policies and procedures to bridge the gap to deliver robust programs to ensure manufacturing environments that are diverse, equitable and inclusive to all.